The Impact of Lifestyle on the Course of Hashimoto’s Disease: The Role of Diet, Physical Activity, and Stress - A Literature Review - Podolska, Alicja; Woźniacka, Agnieszka; Boba, Barbara; Chojnacka, Barbara; Wątor, Julia; Krzeszowiak, Jerzy; Ożga, Aleksandra; Kolano, Patrycja; Bryksy, Sylwia; Pulanecki, Tomasz (Quality in Sport, 2025)
Introduction and purpose of the work: Hashimoto’s thyroiditis (HT), also called chronic autoimmune lymphocytic thyroiditis, is a major cause of hypothyroidism in iodine-sufficient areas. It affects women more often and may co-occur with other autoimmune diseases. HT involves T-cell mediated damage to thyroid cells and the presence of anti-TPO and anti-Tg antibodies. While levothyroxine restores hormone levels, many patients still report fatigue, mood issues, and cognitive problems. This review examines how lifestyle factors—diet, exercise, and stress—affect the course of HT and patient outcomes. State of knowledge: Environmental and behavioral factors are increasingly recognized in autoimmune disease progression. Diets high in processed foods and low in micronutrients may promote inflammation and gut imbalance, worsening autoimmunity. Sedentary behavior and chronic stress also impair immune function. On the other hand, anti-inflammatory diets, physical activity, and stress management may support immune balance and complement standard HT treatment. Materials and methods: A literature review was conducted in PubMed for studies up to 2025, including reviews, original articles, and observational studies in English focused on lifestyle factors in HT. Summary: Lifestyle changes—such as anti-inflammatory diets (e.g., Mediterranean, AIP), regular physical activity, and stress reduction—can improve symptoms and modulate disease markers in HT. These findings support integrating holistic strategies into patient care.